Successive Interference Reduction in Multi User MIMO Channels Using DCI - SureshKumar, K; S.Santhosh Phani Raj, B; B.Sindhush, K; Bhanu Prakash, D; Manoj Kumar, S (International Journal of Engineering and Technology, 2018)
Propelled by the accomplishment of Dahrouj and Yu in connecting the Han-Kobayashi transmission management for mitigating the inter-cell interference in a multi-cell multiple-use multiple in single out interference mesh, this bi-parted messages into privacy and general address in a multi-cell multi-user MIMO IN. In particular, the co-variances of the private and public messages are superintend to optimize either the sum rate or the minimal rate . The public and private messages are decoded in sequence using successive decoding. It reveals how hard to optimize problems can be adequately interpreted by D.C optimization over a simple convex set. Theoretical and simulated outputs shows the use of our proposing solutions for diverse types of Interference networks. In the superintend system, messages are fragmented into private message and public messages. In accordance to optimize the sum rate and minimal rate, co-variances of private and public messages are estimated. The successive decoding algorithm proposed for decoding both private and public messages. The optimization problems will apparent up by accomplishing the difference of concave functions (D.C). Developing a potent D.C optimization network, which is furnished over certain area of bi-parted the private and public rates in several users Multi-Input Multi-Output Interference networks for decreasing the sum rate and minimal user rate. Han Kobayashi (HK) rate bi-parting scheme is exposed as the best plan to mitigate the interference and increase the performance.
Keywords: Interference; decoding; mitigation; sum rate; minimal rate; beam forming.